Sweden regarding immigration: development and evolution of a multicultural policy. - López Sala, Ana María (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
Sweden has been one of the european countries where the multicultural principle has got more political influence. In 1975 a Multicultural Policy was adopted by Parliament. The contents of the new policy were condensed in terms of three slogans: equality, freedom of choice and partnership - a radical break from the traditionally unreflected policy of assimilation. This ideal affected the construction and policy-making process of Immigration and Immigrant Policy. In this paper, I will discuss how the situation has development over the past twenty years and show some reflections which let us to support the inevitable outcome, the fail of this kind of policy and some of their goals in this nordic country.